DAMPAK GLOBALISASI, DETERMINAN SOSIAL KESEHATAN DAN TUJUAN PEMBANGUNAN SOSIAL TERHADAP KESEHATAN GLOBAL DI INDONESIA - Langingi, Nova Lina (JURNAL KEPERAWATAN MUHAMMADIYAH BENGKULU, 2023)
Globalization is both simplifying yet a complicated health issue. It makes everything farther, faster, cheaper and deeper and serves as double edged-sword to health, as it provides extremely positive and extremely negative impacts on health in which health appointments is readily available on “click” requests, yet it makes fast food readily available, and that impacts on worsening sedentary lifestyle and other less healthy habits resulting ultimately in various health consequences to be brought into existence called “man-made diseases.” The establishment of Social Determinants on Health (SDH) and Social Developmental Goals (SDGs) needs to be reviewed in regards to the impact towards global health in the globalization perspective. This study is a narrative literature review on the impact of globalization, social determinants on health and social developmental goals on global health. The keywords are “globalization”, “social determinants on health”, “social developmental goals” and "global health” related articles browsed in Google search engine throughout all periods of time in Bahasa Indonesia or English as the criteria of articles used. The literature showed that while globalization provides faster and advanced medical service, sedentary lifestyle, loneliness, climate changes resulting in disasters and other innumerable diseases are on the rise. Social determinants on health are narrowing into “windows” or “tabs”, as the social media provide an easier way to socialize to work, play, live and age. Sustainable development goals on health in which the other Social Determinants on Health (SDH) are relying upon are not progressing rapidly, and even worse in some aspects. The United Nations, nation leaders and other stakeholders were kept on trying and trying multiple strategies and amending the laws, policies and finding the best ways they can afford to solve these problems, thus, attaining the sustainable development goals.